2011
DOI: 10.1007/s00464-011-2050-1
|View full text |Cite
|
Sign up to set email alerts
|

Transoral incisionless fundoplication (TIF 2.0) with EsophyX for gastroesophageal reflux disease: long-term results and findings affecting outcome

Abstract: TIF using the EsophyX device allowed withdrawal or reduction of PPI in about 77% of patients at 6-month follow-up and about 69% at 24 months. Larger number of fasteners deployed during TIF was predictive of positive outcome; pre-TIF ineffective esophageal motility and hiatal hernia raised the risk of recurrence of GERD symptoms, but were not significant from a prospective point of view.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 33 publications
4
36
0
1
Order By: Relevance
“…Recent alternative approaches have included transoral incisionless fundoplication, a suturing device designed to create a full thickness gastroesophageal valve from inside the stomach. Unfortunately long-term data regarding efficacy of this device are limited to a small number of subjects and short duration of follow-up ( 97 ). A recent study suggested that at 36 months of follow-up, the majority of patients had required additional medical therapy or a revisional fundoplication ( 98 ).…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…Recent alternative approaches have included transoral incisionless fundoplication, a suturing device designed to create a full thickness gastroesophageal valve from inside the stomach. Unfortunately long-term data regarding efficacy of this device are limited to a small number of subjects and short duration of follow-up ( 97 ). A recent study suggested that at 36 months of follow-up, the majority of patients had required additional medical therapy or a revisional fundoplication ( 98 ).…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…They are classified into three categories. The first is a method to generate plication on cardia [166][167][168][169][170]. The second involves alteration of muscle layer on LES [171], and the third involves insertion of foreign bodies into LES [172,173].…”
Section: Cq: Is Laparoscopic Fundoplication Useful Compared With Openmentioning
confidence: 99%
“…Six months after TIF, GERD symptoms had improved according to the reduction in GERD-HRQL scores (from 26 [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]) to 10 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], P < 0.01). Common use of acid suppressive medication was discontinued by 67% of patients, whereas 19% used PPIs occasionally and common use was present in 14%.…”
Section: Patient Characteristics and Symptom Scoresmentioning
confidence: 99%
“…[6][7][8] Previous studies have attempted to identify patient characteristics and objective parameters like lower esophageal sphincter (LES) resting pressure and the number of fasteners that may help to predict treatment outcome of the TIF procedure. 9,10 However, up to now, no objective parameter is available to select patients for this endoluminal procedure. Increased esophagogastric junction (EGJ) distensibility is considered a pathophysiologic factor in GERD as EGJ compliance determines the opening diameter of the EGJ and consequently the volume of reflux content into the esophagus.…”
Section: Introductionmentioning
confidence: 99%